THE INFLUENCE OF WORK MOTIVATION AND WORK ENVIRONMENT ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR WITH JOB SATISFACTION AS AN INTERVENING VARIABLE AT THE YOUTH AND SPORTS OFFICE OF NORTH SUMATRA PROVINCE - Farisi, Salman; Andi Prayogi, Muhammad; Juliana, Elfi (CV. Radja Publika, 2021)
This study aims to determine the effect of work motivation and work environment on organizational citizenship behavior in mediating job satisfaction at the Youth and Sports Office of North Sumatra Province. In this study using associative research with a sample of 52 respondents who are employees of the Department of Youth and Sports of North Sumatra Province. Data collection techniques using questionnaires and data analysis techniques using Partial Least Square (SmartPLS) to test the seven hypotheses proposed in this study. The results of this study indicate that the effect of motivation on satisfaction has a positive and not significant effect; the influence of motivation on OCB has a positive and significant effect; the influence of the environment on satisfaction has a positive and significant effect; environmental influence on OCB has a negative and insignificant effect; the effect of satisfaction on OCB has a positive and significant effect; the effect of motivation on OCB mediated by satisfaction has no significant effect, which means that job satisfaction does not play a role in mediating work motivation on OCB; The influence of the environment on OCB mediated by satisfaction has a significant effect, which means that job satisfaction plays a role in mediating the work environment on OCB.